ICT Adoption in Executive Training for Development: Blending Digital and Physical Communication and Awareness Channels - Ferraud, Geneviève; Holzer, Adrian; Gillet, Denis (: ACM, 2019)
Digital capacity building is a key policy for states to meet the Sustainable Development Goals. This paper1 presents one of the actions carried out by the United Nations Conference on Trade and Development (UNCTAD) in collaboration with the Swiss Federal Institute of Technology in Lausanne (EPFL) to tackle the multifaceted digitization challenges in developing and transition economies by introducing blended learning in one of its flagship executive courses. The main outcome is the obvious but generally neglected importance of focusing on the added values, the competence de- velopment, and confidence building for all stakeholders to trigger adoption. These objectives are partially tackled by blending digital and physical communication and awareness channels in face-to-face executive training sessions.
, 2019